Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1177/002221949803100605
|View full text |Cite
|
Sign up to set email alerts
|

The Irvine Paraprof essional Program

Abstract: The Irvine Paraprofessional Program (IPP) looks promising for serving elementary-school children with attention-deficit/hyperactivity disorder (ADHD) in the general education classroom. This article describes the components of the IPP, preliminary research studies that support its efficacy, and the benefits of the model. The IPP is a 12-week intensive intervention that includes (a) direct intervention to children with ADHD by specially trained paraprofessionals, (b) teacher consultation by the school psycholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The social skills curriculum that was implemented in each of the children's therapeutic group sessions was originally developed for the UC Irvine Child Development Center School Program, a laboratory school environment for children with ADHD. This model combines strategies based in learning and cognitive-behavioral theories and is aimed to promote adaptive skill acquisition and thereby reduce problem behaviors ( 36 ). This curriculum, along with the curriculum of the Summer Treatment Program developed by Pelham et al ( 37 ) contributed to the psychosocial treatment strategies implemented and tested in the Multi-modal Treatment Study of ADHD (MTA Study), the largest NIH funded longitudinal study of treatment modalities for children with ADHD ( 38 40 ).…”
Section: Methodsmentioning
confidence: 99%
“…The social skills curriculum that was implemented in each of the children's therapeutic group sessions was originally developed for the UC Irvine Child Development Center School Program, a laboratory school environment for children with ADHD. This model combines strategies based in learning and cognitive-behavioral theories and is aimed to promote adaptive skill acquisition and thereby reduce problem behaviors ( 36 ). This curriculum, along with the curriculum of the Summer Treatment Program developed by Pelham et al ( 37 ) contributed to the psychosocial treatment strategies implemented and tested in the Multi-modal Treatment Study of ADHD (MTA Study), the largest NIH funded longitudinal study of treatment modalities for children with ADHD ( 38 40 ).…”
Section: Methodsmentioning
confidence: 99%
“…TwohundredandsixteenundergraduatestudentsattendingaUnitedStates-baseduniversityvoluntarily tookpartinthecurrentstudy.Studentsrepresentanimportantpartoftheonlinepopulation,andseveral studies,e.g., (Dai&Salam,2009;Houston&Taylor,1999;Kovar,Burke&Kovar,2000)haveutilized themassubjectsinstudiesofonlineconsumers.Infact,studentsandnon-studentshavedemonstrated identicalpatternsofbehaviorintheonlineenvironment (Ahuja,Gupta&Raman,2003).Indeed, onlineconsumersaregenerallyyoungerandmoreeducatedthanconventionalconsumers (Kotkin, 1998;Kimetal.,2007);thus,collegestudentsaregoodrepresentativesoftheonlinepopulation.In thecurrentstudy,99%ofrespondentswereinthe18-25agegroup,86respondentswerefemales, and123respondentsweremales.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have found that brief training can generate significant improvements in school staff knowledge. This has been investigated in suicide ( 12 14 ), ADHD ( 15 17 ), mental health first aid ( 18 ), and deliberate self-harm ( 19 ) with good results.…”
Section: Introductionmentioning
confidence: 99%